Martelli Chaotic Properties of a Generalized Form of Zadeh’s Extension Principle - Yaoyao Lan; Chunlai Mu (Journal of Applied Mathematics)
Let X denote a compact metric space and let f : X→X be a continuous map. It is known that a discrete dynamical system (X,f) naturally induces its fuzzified counterpart, that is, a discrete dynamical system on the space of fuzzy compact subsets of X. In 2011, a new generalized form of Zadeh’s extension principle, so-called g-fuzzification, had been introduced by Kupka 2011. In this paper, we study the relations between Martelli’s chaotic properties of the original and g-fuzzified system. More specifically, we study the transitivity, sensitivity, and stability of the orbits in system (X,f) and its connections with the same ones in its g-fuzzified system.